PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA UNIT GROUND SUPPORT EQUITMENT (GSE) PT.GAPURA ANGKASA CABANG DENPASAR - I Dewa Made Sanaputra; I Ketut Setia Sapta; I Nengah Sudja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
This study aims to determine the effect of work environment, work motivation, and work discipline on employee performance. This research was carried out at Ground Support Equitment (GSE) of PT. Gapura Angkasa, Denpasar Branch. Sampling in this research is the entire population at the Ground Support Equitment (GSE) unit of PT. Gapura Angkasa, Denpasar Branch, totaling 35 people. Methods of data collection using questionnaires and interviews. The data analysis used in this research is descriptive analysis and inferential analysis to determine the effect of work environment, work motivation, and work discipline on employee performance. The results showed that the work environment has a positive effect on employee performance, work motivation has a positive effect on employee performance and work discipline has a positive effect on employee performance at the Ground Support Equitment (GSE) unit of PT. Gapura Angkasa, Denpasar Branch.